A new bronchoscopic catheter for the transbronchial ablation of pulmonary nodules. (October 2018) - Safi, Seyer; op den Winkel, Jan; Kramer, Steve; Keast, Thomas; Wibowo, Henky; Muley, Thomas; Herth, Felix J.F.
Highlights: Numerous patients with malignant pulmonary nodules cannot tolerate surgery. Recently, peripheral bronchoscopy made it possible to assess pulmonary nodules. We developed a radiofrequency catheter that is compatible with most bronchoscopes. Bronchoscopic ablation may be the least invasive treatment option. Abstract: Objectives: With the objective of simultaneous bronchoscopic biopsy and ablation of malignant solitary pulmonary nodules, we have developed a flexible monopolar radiofrequency (RF) catheter that can be deployed through the working channel of most bronchoscopes. Materials and Methods: Fresh tumor specimens were heated in a water bath to 37 °C, and the RF catheter was inserted into the tumors within the specimen. Temperature sensors were positioned 3 mm, 5 mm and 7 mm from the electrode to measure the temperature of the surrounding tissue every 1 s. The ablation was conducted by applying RF energy for 8 min. The ablated specimens were evaluated by cutting the tissue samples along the top of the device and measuring the ablation zones. Results: Five ablations were performed in 3 specimens. All of the ablation zones had a major axis length (along the electrode axis) between 18.9 mm and 22.8 mm and a minor axis length (perpendicular to the major axis) between 13.3 mm and 18.0 mm. The temperature data showed that all of the temperature sensors detected 60 °C or higher. These results demonstrate that the RF catheter was capable of generating ablation zones that were locally contained in ex vivo human cancerous lung specimens and that incorporated the tumor tissues. Conclusion: We present the results of a benchtop study demonstrating the local control of ablation achieved using the RF device. This study suggests that the ex vivo ablation of lung malignancy with a new bronchoscopic RF catheter is feasible and that in vivo tumor ablation with this method in humans merits further study.